Integrated marketing communication: need, approaches, and issues - a research perspective - Agrawal, Anand; Agrawal, Preeti (2006)
This article aims at presenting a bird's eye view on the needs, approaches and issues related to Integrated Marketing Communication (IMC) with a research perspective. This can help the researchers to carry out the literature survey. This account traces the history of IMC and the different needs and models evolved, leading to the use of IMC as a prevalent marketing communication form. Some problems of integration are also discussed in the article. - Reproduced.
Keywords: Marketing